Cardiovascular health among two ethnic groups living in the same region: A population-based study. (1st February 2017) - Benderly, Michal; Chetrit, Angela; Murad, Havi; Abu-Saad, Kathleen; Gillon-Keren, Michal; Rogowski, Ori; Sela, Ben-Ami; Kanety, Hannah; Harats, Dror; Atamna, Ahmed; Alpert, Gershon; Goldbourt, Uri; et al.
Abstract: Background: Poor cardiovascular health (CVH) among ethnic/racial minorities, studied primarily in the USA, may reflect lower access to healthcare. We examined factors associated with minority CVH in a setting of universal access to healthcare. Methods and results: CVH behaviors and factors were evaluated in a random population sample (551 Arabs, 553 Jews) stratified by sex, ethnicity and age. More Jews (10%) than Arabs (3%) had 3 ideal health behaviors. Only one participant had all four. Although ideal diet was rare (≤ 1.5%) across groups, Arabs were more likely to meet intake recommendations for whole grains, but less likely to meet intake recommendations for fruits/vegetables and fish. Arabs had lower odds of attaining ideal levels for body mass index and physical activity. Smoking prevalence was 57% among Arab men and 6% among Arab women. Having four ideal health factors (cholesterol, blood pressure, glucose, smoking) was observed in 2% and 8% of Arab and Jewish men, respectively, and 13% of Arab and Jewish women. Higher prevalence of ideal total-cholesterol corresponded to lower high-density lipoprotein cholesterol among Arabs. No participant met ideal levels for all 7 metrics and only 1.8% presented with 6. Accounting for age and lower socioeconomic status, Arabs were less likely to meet a greater number of metric goals (odds ratio (95% confidence interval): 0.62 (0.42–0.92) for men, and 0.73 (0.48–1.12) for women). Conclusions: Ideal CVH, rare altogether, was less prevalent among the Arab minority albeit universal access to healthcare. Health behaviors were the main contributors to the CVH disparity.